Commissioning the FAst TIMing array (FATIMA) at FAIR Phase-0: Half-lives of excited states in the N=50 isotones 96Pd and 94Ru. (November 2022) - Jazrawi, S.; Yaneva, A.; Polettini, M.; Das, B.; Regan, P.H.; Górska, M.; Cederwall, B.; Jolie, J.; Albers, H.M.; Chishti, M.M.R.; Banerjee, A.; Hubbard, N.; et al.
Abstract: This paper reports results of the first experiment of the DESPEC Phase-0 campaign at GSI, which focused on the study of neutron-deficient nuclei approaching 100 Sn. These data provide the first extended commissioning experiment for the DESPEC collaboration within NuSTAR. We present results on electromagnetic transition rates associated with the decays from excited states populated following the formation of I π = 8 + proton 'seniority-isomer' states in the N = 50 isotones 94 Ru and 96 Pd. Direct half-life measurements via γ−γ coincidences using the FATIMA detector array consisting of 36 LaBr3 (Ce) scintillators have determined the reduced matrix elements associated with decays between low-lying states in these semi-magic nuclei. The extracted half-lives for yrast I π = 6 + and 4 + states in 96 Pd and the 6 + state in 94 Ru are consistent with the published, highest-precision values for these nuclei. Highlights: B(E2) values measured for 94 Ru and 96 Pd using fast-timing gamma-ray spectroscopy. Commissioning run of the Decay SPECtroscopy (DESPEC) collaboration at FAIR-0. Precision measurement of prior reported excited state half-lives in 94 Ru and 96 Pd.